PENERAPAN TEKNOLOGI RIA UNTUK MEMBANGUN APLIKASI WEB DENGAN PENGAKSESAN REALTIME (Studi Kasus : Pemesanan Handphone Online) - Fiftin Noviyanto; Ahmad Ashari (Jurnal Informatika, 2011)
Today Web technology allow web visitor to interact fully to web basedsystem. The interaction accessibility development aims to make it moreattractive and make visitor easier in system usage. One of advantages of webbased application is easiness in accessing data that not limited to place andtime, while its disadvantage is waiting time for processing user request, somore time process in web application called then required waiting time ismore. It is different from desktop based application that require applicationinstallation in computer used to access data, however, it has advantage inexecution process of real-time instruction, without requiring data accesswaiting time to server. This research has succeeded in applying RIAtechnology to build web with instruction response capability same as desktopapplication in case study of cellular phone reservation. Built system includedcatalog presentation, filterization, comparation, shopping basket andreservation process. Built application consisted of some layers including dataalter as reservation system data storage, presentation later to present productand control layer to manage instruction response.Â